2019
DOI: 10.1016/j.ecolind.2019.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Land use effects in riverscapes: Diversity and environmental drivers of stream fish communities in protected, agricultural and urban landscapes

Abstract: Increasing agriculture and urbanization inevitably lead to changes in the biodiversity of stream ecosystems. However, few studies examined comprehensively how biodiversity is distributed within and among protected, agricultural and urban land use types in streams. We studied environmental characteristics of streams and patterns of species richness and other community attributes of stream fish communities in these three characteristic land use types in the catchment of the Danube River, Hungary. Land use separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…These results suggest the relatively low predictability of stream fish assemblages in this human-modified landscape (see also Erős et al, 2012), or at least that urbanization in itself was an insufficient predictor of fish assemblage characteristics. Our findings thus confirm other studies, which found highly variable and sometimes even weak responses of fish to land use gradients (e.g., Utz et al, 2010;Tóth et al, 2019). In contrast, most studies showed clear negative influence of increasing urbanization on fish assemblages (Helms et al, 2005;Morgan and Cushman, 2005;Slawski et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results suggest the relatively low predictability of stream fish assemblages in this human-modified landscape (see also Erős et al, 2012), or at least that urbanization in itself was an insufficient predictor of fish assemblage characteristics. Our findings thus confirm other studies, which found highly variable and sometimes even weak responses of fish to land use gradients (e.g., Utz et al, 2010;Tóth et al, 2019). In contrast, most studies showed clear negative influence of increasing urbanization on fish assemblages (Helms et al, 2005;Morgan and Cushman, 2005;Slawski et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, we could characterize only a relatively short urbanization gradient, due to the lack of large metropolitan areas in Hungary, not like those found in other countries (e.g., USA). Nevertheless, documenting patterns and understanding processes in the early phase of urbanization is important to provide evidence for possible future effects, especially since urbanization processes are ongoing intensively in this region (Tóth et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urbanised landscapes have been associated with a variety of changes to stream habitats including increased nutrient input, sedimentation, runoff, and channelisation (Allan, 2004). Decreases in species richness associated with increased urban land use has been documented for fish communities across the globe (Edge et al., 2017; Tóth et al., 2019; Wang et al., 2001). Even if regional species pools are similar, unique species groupings can still be observed in metacommunities because of interspecific differences in tolerance to urbanisation (Utz et al., 2010), which is a similar notion to why urbanisation could impact turnover (Johnson et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Habitat modifications in upland streams associated with anthropogenic activities may cause endemic fish species population declining and even local extinguishing (Dorobek et al, 2015;Tóth et al, 2019), which further alters both taxonomic and functional compositions (Dala-Corte et al, 2016;Leitão et al, 2018). However, habitat modifications may also favor the occurrence and spread of alien and/or native invaders into upland streams (Scott & Helfman, 2001;Dala-Corte et al, 2019).…”
Section: Discussionmentioning
confidence: 99%